O METODO DA FLUORESCEINA NA AVALIACAO DE AREAS DE ISQUEMIA EXPERIMENTAL DO MIOCARDIO NO CAO - De Abreu Maffei, F. H.; De Franco, M. F.; Hossne, W. S. (My University, 1973)
Focal myocardial ischemia was provoked in 70 dogs by ligature of the anterior descending branch of the left coronary artery and by means of circular superficial complete or incomplete suture around an area of the anterior wall of the left ventricle. A 5% fluorescein solution was administered intravenously immediately afterwards; the heart was exposed and the room darkened, illuminated by ultraviolet light. Dogs were sacrificed immediately and the heart examined both gross and microscopically; other animals were reoperated 22 hr and 7 days after the first surgery. Fluorescein was administered under the same conditions as of the first operation and the animals were then sacrificed and the hearts examined. Fifteen dogs were used as a control group. The method is safe and may be of use in the diagnosis, localization and evaluation of the extension and evolution of ischemic areas of the heart, in vivo. The method described may prove useful in the intraoperative evaluation of revascularization of ischemic areas. Moreover, the method may be used in other necessary intraoperative evaluations of heart irrigation.
An evaluation of experimental myocardial ischemia in dogs by means of the fluorescein method